KEMAMPUAN MENENTUKAN KONJUNGSI PADA KALIMAT MAJEMUK SISWA KELAS VIII SMP BUDI DHARMA KOTA DUMAI - Normasari, Siti; Hakim, Nursal; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Research on the ability to determine the conjunction in compound sentences is a quantitative descriptive study. The reason author examines the use of conjunctions, the first use of conjunctions is very important in oral and written communication, but there are still many people who are wrong and incorrect in using or placing the conjunction in oral and written language. Both of the learning about the use of conjunctions were studied by students of class VIII, research on the ability to determine conjunctions has not been done in Junior High School Budi Dharma Dumai. The focus in this research is, (1) The ability to determine conjunctions in the coordinating sentences of grade VIII students of Junior High School Budi Dharma Dumai, (2) The ability to determine the conjunctions in subordinative sentences of grade VIII students of Junior High School Budi Dharma Dumai, (3) The ability to determine the conjunctions in correlative sentences class VIII students of Junior High School Budi Dharma Dumai. Key Words: Conjunction, Compound Sentence, Coordinative, Subordinative, and Correlative